SmartCity: Public Transportation Network Planning Based on Cloud Services, Crowd Sourcing and Spatial Decision Support Theory - Frez, Jonathan; Baloian, Nelson; Zurita, Gusravo (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
Cities are growing and the number people using smartphone’s and tablets it also increasing. There are many applications that collects data from users and its context. Some of these applications are producing complete and useful databases that can be used to support some cites problems. In particular spatial planning problems like transportation network planning. In this work we presented a method to use existing crowdsourcing data and cloudservices to support a transportation network decision making process. The method is based the Dempster-Shafer Theory to combine the different sources information and to model transportation demand.